1985
DOI: 10.1016/s0022-5347(17)49332-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry of Ethanol-Fixed Versus Fresh Bladder Barbotage Specimens

Abstract: Saline bladder barbotage specimens were obtained from 99 patients for comparison of flow cytometric deoxyribonucleic acid analyses using fresh versus ethanol-fixed cell preparation techniques. The analyses were consistent for the 2 methods in 87 (88 per cent) of the 99 cases (p less than 0.0001, Kappa statistic for agreement). Since accurate, reproducible results are obtainable on fixed bladder washings, samples may be sent to flow cytometry centers for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Two of them were performed using flow cytometric technique and ethanol solution at a relatively high concentration. 11,12 Another study used image analysis and 25% ethanol (final concentration), the same concentration used in our study. 13 The higher concentration of ethanol might have provided better-quality cell preservation than the lower concentration did, but the higher concentration of ethanol solution makes the cells less adhesive to the surface of glass slides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them were performed using flow cytometric technique and ethanol solution at a relatively high concentration. 11,12 Another study used image analysis and 25% ethanol (final concentration), the same concentration used in our study. 13 The higher concentration of ethanol might have provided better-quality cell preservation than the lower concentration did, but the higher concentration of ethanol solution makes the cells less adhesive to the surface of glass slides.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no published data exist on the usability of urine samples obtained for urine cytologic examination from outreach patients, although a few studies of DNA ploidy on ethanol-fixed urine specimens have been reported. [11][12][13] The American Society of Cytopathology recently discussed online the fixatives for urine cytology for outreach patients, indicating that the method is not well known or widely used. In this article, we present our results of cytologic diagnosis in conjunction with DNA image analysis on urine specimens fixed with an equal volume of 50% ethanol and submitted through a mailer system at ambient temperature.…”
Section: Use Of Mailed Urine Specimens In Diagnosingmentioning
confidence: 99%
“…Several other studies describe intra-laboratory comparisons of different methods and variants of techniques for quantitative analysis of ploidy and proliferation (2,6,7,12,16,19,25,27,32,33,35,36,38,39,43,46,51). These reports compare the analyses of fresh and paraffin-embedded tissues (2,6,25,33,51), fresh and ethanol-fixed tissues (2,35), and ethanol-pepsin and Formalin-subtilisin Carlsberg-treated tissues (7).…”
mentioning
confidence: 99%
“…These reports compare the analyses of fresh and paraffin-embedded tissues (2,6,25,33,51), fresh and ethanol-fixed tissues (2,35), and ethanol-pepsin and Formalin-subtilisin Carlsberg-treated tissues (7). Other methods that have been compared include an automated mechanical disaggregation method and fine-needle aspiration (33), microspectrophotometric and flow cytometric analysis (16,38), static cytophotometry and flow cytometry (51), fluorescence image cytometry and flow cytometry (46), 3 H-ThdR labeling and S-phase analysis by flow cytometry (19), and BrdUrd labeling and S-phase analysis by DNA flow cytometry (12,32,36,39,43).…”
mentioning
confidence: 99%